Implementation Of Law Number 6 Year 2011 Concering Immigration Administrative Actions Against Policies Applicable At The Immigration Office - Achmad Aziz; Ady Arif; Gyan Samladandi Gumay (IHSA Institute, 2021)
The purpose of this research is to explain, analyze, and develop the law in immigration. Indonesia's strategic geographical location has always been a crossroads of world traffic, both air and sea traffic, it cannot be denied because of the strategic location of the Indonesian state, the traffic of foreigners entering or leaving the territory of the Indonesian state is very congested, foreigners entering the country are very dense. Indonesian territory certainly has goals and interests, thus immigration has a function to maintain the upholding of the sovereignty of the Indonesian state. In order to realize the principle of